2014
DOI: 10.5433/1679-0359.2014v35n3p1425
|View full text |Cite
|
Sign up to set email alerts
|

Acúmulo de massa seca em cultivares de Brachiaria brizantha submetida a intensidades de desfolhação

Abstract: ResumoO experimento foi realizado com o objetivo de avaliar o efeito de diferentes intensidades de desfolhação no acúmulo de matéria seca, composição morfológica e resíduo de forragem de cultivares de Brachiaria brizantha. Os tratamentos consistiram em três cultivares de Brachiaria brizantha (Marandú, Xaraés e MG4) e quatro intensidades de desfolhação (10, 20, 30 e 40 cm) durante o período de agosto de 2010 a julho de 2011. O delineamento experimental foi o de blocos casualizados com quatro repetições em fator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 15 publications
0
13
0
3
Order By: Relevance
“…Pasture management needs to be oriented towards factors related to plant, animal, and forage quantity and quality (LIMA et al, 2014). Grass height control is part of such management and influences forage structure and quality due to changes in fiber quantity, which affects food intake dynamics and animal performance (FONTES et al, 2014;VAN SOEST, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Pasture management needs to be oriented towards factors related to plant, animal, and forage quantity and quality (LIMA et al, 2014). Grass height control is part of such management and influences forage structure and quality due to changes in fiber quantity, which affects food intake dynamics and animal performance (FONTES et al, 2014;VAN SOEST, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of SM exhibited quadratic behavior (P < 0.05) for RP 28days , with a minimum of 3.67% when 297.5 kg N ha -1 was applied (Figure 3f). Fontes et al (2014) reported that higher grazing intensities promoted an increase in the proportion of stems in the botanical composition of the pasture. The authors stated that this leads to lower forage density and a higher leaf:stem ratio at greater heights.…”
Section: Resultsmentioning
confidence: 99%
“…After fitting to the quadratic model, the period showed maximum forage density of 182.05 kg ha -1 cm -1 for 111.87 kg N ha -1 . Forage density determines intake rates in tropical pastures along with the leaf:stem ratio (FONTES et al, 2014). Costa et al (2010) stated that nitrogen fertilization is a management strategy that promotes an increase in forage density and leaf production, positively influencing DM production.…”
Section: Resultsmentioning
confidence: 99%
“…It has horizontal, short, tough and curved rhizomes. It has deep roots, which help them to survive along dry periods (FONTES et al, 2014).…”
Section: Introductionmentioning
confidence: 99%